2002
DOI: 10.1149/1.1491335
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Electrodeposited Cobalt

Abstract: The structure of cobalt formed by electrodeposition and the influence of the pH of the plating solution and the cathode potential was studied by potentiodynamic measurements and X-ray diffraction. It was found that the level of overpotential significantly affects the structure of the formed cobalt. When electrodeposition is performed far from equilibrium conditions, i.e., at a high overpotential, face-centered cubic ͑fcc͒ cobalt is deposited while at low overpotential hexagonal close packed Co is formed with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 15 publications
4
45
0
Order By: Relevance
“…Under equilibrium conditions at room temperature, the Co metal exists in the hcp phase though the fcc phase is stable above 420°C only [30]. It is known that electrochemical deposition from a bath at pH more than 2.9 results mainly in hcp-Co [31,32]. However, in the literature, the formation of fcc-Co phase by electrodeposition at room temperature is due to the presence of codischarged and dissolved hydrogen distorting the hcp lattice to an extent that it finally transformed to the fcc structure [33].…”
Section: Resultsmentioning
confidence: 99%
“…Under equilibrium conditions at room temperature, the Co metal exists in the hcp phase though the fcc phase is stable above 420°C only [30]. It is known that electrochemical deposition from a bath at pH more than 2.9 results mainly in hcp-Co [31,32]. However, in the literature, the formation of fcc-Co phase by electrodeposition at room temperature is due to the presence of codischarged and dissolved hydrogen distorting the hcp lattice to an extent that it finally transformed to the fcc structure [33].…”
Section: Resultsmentioning
confidence: 99%
“…The hcp phase, having hexagonal symmetry axis nearly perpendicular to the wire axis, favours a transverse easy magnetization axis. [8] Bulk hcp cobalt presents crystalline anisotropy constant K 1 » 5 10 5 J/m 3 at room temperature, which nearly balances the shape anisotropy, K s » p l 0 M s 2 = 6 10 5 J/m 3 squareness ratio that converts Co into an unsuitable element for arrays of magnetic nanowires. In order to overcome this situation, the growing of Co with fcc crystalline phase is highly desirable since in that case the easy magnetization axis lies nearly parallel to the wire axis, [9] which added to the shape anisotropy strongly favours a resulting longitudinal magnetic anisotropy so, enhancing the squareness of hysteresis loops.…”
mentioning
confidence: 99%
“…On the other hand, Cohen-Hyams et al have found that Co can be electrodeposited into both hcp and fcc structures from a neutral bath (pH 7), depending on the cathode potential. [8] The level of overpotential significantly affects the structure of the formed cobalt. When the electrodepostion is performed far from the equilibrium conditions, fcc cobalt is deposited while at equilibrium conditions hexagonal close packed Co is formed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The low pH of the electrolyte enhances the evolution of hydrogen gas and the Co ion mobility during the electroplating process. The enhanced atomic mobility may be equivalent to a high temperature condition so that the FCC phase can be obtained (Cohen-Hyams et al, 2002). Nevertheless, the coexistence of both Co crystal phases has been reported in different works (Ye et al, 2009;Sánchez-Barriga et al, 2009).…”
Section: Cobalt Nanowiresmentioning
confidence: 97%